Development and evaluation of checklists to support the recruitment of committed hematopoietic stem cell donors. Issue 4 (19th February 2022) - Fingrut, Warren B.; Chen, Angela C.; Green, Meagan; Weiss, Jason T.; Mercer, Dena; Allan, David
Abstract: Background: Checklists are memory recall tools used across healthcare to improve outcomes. Here, we describe the development and evaluation of checklists to support recruitment of committed allogeneic hematopoietic stem cell donors. Study Design and Methods: Checklists were developed with the following objectives: (1) improve best‐practice adherence; (2) reduce errors; and (3) support standardization at stem cell drives. Topics included: recruiting needed donors; securing informed consent; maintaining good‐documentation practices; and supervising registration and tissue sample collection. Checklists were iteratively revised with input from stakeholders. We evaluated the checklists by examining recruitment outcomes and errors (i.e., preventing registrants from being listed as donors) pre‐ (11/2011–8/2016) and post‐ (9/2016–11/2019) implementation by the Canadian donor recruitment organization Stem Cell Club. Quantitative and qualitative methods were employed to analyze recruiters' perspectives on the checklists. Results: The checklists supported recruitment of donors from needed demographic groups as Stem Cell Club expanded its recruitment effort from 4118 registrants (60% male, 58% non‐European) pre‐implementation to 10, 621 (52% male, 56% non‐European) post‐implementation. Checklist implementation was associated with a marked reduction in errors (from 13.2% to 1.9%) and a three‐fold increase in the match rate of recruited donors (from 0.024% to 0.075%). Qualitative and quantitative analysis of recruiter feedback supported that the checklists' objectives were realized from the recruiter perspective. Discussion: We developed checklists to support donor recruitment and showed that their implementation was valued by recruiters and associated with both reduced errors and improved donor recruitment outcomes. The checklists are relevant to donor recruitment organizations worldwide.